STRATEGIC MANAGEMENT PRACTICES ORGANIZATION OVER EMPLOYEE OWNERSHIP EFFECTS ON PERFORMANCE: A RESEARCH ON PRIVATE INSTITUTIONS PROVIDING HIGHSCHOOL AND MIDDLE SCHOOL EDUCATION IN ISTANBUL (Third Sector Social Economic Review, 2021)
The phenomenon of management is a historical and universal phenomenon since theworld exists to this day. In the light of changes and developments in the political, economic, technological and socio-cultural fields in the world along with globalization, the understanding of management is also changing naturally. The phenomenon of change is a universal phenomenon that does not change, institutions and organizations need to choose a management method that will give them the ability to manage change in the face of change.The positive effects of the Strategic Management Process on the development, competitive nessand performance of institutions have been scientifically demonstrated, and employee satisfaction is also considered important in this regard. By drawing attention to the importance of Strategic Management, the role of employee satisfaction in the relationship between organizational performance and organizational performance in private highschool and Secondary School institutions in Istanbul will be tried to be revealed.
Keywords: Strategic Mamagement; Employee Satisfaction; Organizational Performance